Tibetan Buddhism, Wetland Transformation, and Environmentalism in Tibetan Pastoral Areas of Western China - Kabzung Gaerrang (Conservation & Society, 2017)
Alpine wetlands occupy a considerable area of the Tibetan Plateau, a region that is characterised by diverse but fragile ecosystems, including alpine wetlands, which are reported to have shrunk by 29% over the last several decades. This article explores the contradictory practices of Tibetan pastoralists regarding these alpine wetlands and examines how Tibetan pastoralists conceptualise and understand wetlands as well as how state policies, market forces, and religious norms work together to produce Tibetan herders' practices vis-à -vis their livestock and the wetlands. The analysis will first challenge the common notion that Tibetan Buddhism plays a decisive and consistent role in conservation and environmental protection, an idea that has been proposed by academic scholars and promoted by many non-governmental organisation practitioners. As an alternative to the attempt to measure indigenous people and their culture against the criteria set out by western conservation, I argue through this case study that Tibetan pastoralists' relationship with wetlands informs their negotiation with competing forces including state policies, market logics, global environment movements, religious resurgence, and traditional nomadic practices.